Analisis Fashion Influencer Berkontribusi Dalam Purchase Intention Konsumen Tiktokshop - Firda Dwi Rahmawati; Tirton Nefianto (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
The development of the trading industry in the online or e-commerce world which is increasingly rapid and increasingly dynamic encourages economic growth and provides direct and indirect benefits to trading activities. One of the current trading strategies is content marketing with influencers. This study aims to determine the contribution of influencers in the fashion sector in the purchase intention of Tiktok Shop consumers. Data collection was carried out using the method of collecting information through a survey with a questionnaire distributed via social media. The population in this study are users who have used and shopped at the Tiktok Shop application in the Jabodetabek area. Questionnaires collected as many as 170 respondents, the data is then processed by means of multiple linear regression analysis. The results of this study indicate that there is a positive influence of expertise influencer and positive attractiveness influence on purchase intention, while trustworthy is not affected by Purchase Intention.